Ammonia concentration and recovery in an up-scaled electrochemical cell through screening of cation exchange membrane - Choi, Seongmin; Lee, Wonjun; Kim, Hanwoong; Lee, Gwangtaek; Lee, Changsoo; Cheong, Dae-Yeol; Son, Won-Keun; Kim, Kwiyong (Frontiers in Water, 2024)
An intensifying global alarm over excessive total ammonia nitrogen (TAN) calls for innovative recovery strategies. Although electrochemically-driven TAN concentration and recovery have been explored, limited research on upscaling lab-scale advancements with careful system engineering leaves a notable gap in practical application. Here, in the context of implementing an upscaled electrochemical system, we carefully chose a suitable cation exchange membrane to ensure the best ammonium migration, energy efficiency, and stability. Systematically examining the effects of applied current density and loading rate using Neosepta CSE, we achieved final concentrated TAN levels in the receiving catholyte, reaching 836.7 mM (4.4-fold), 778.8 mM (3.5fold), and 980.4 mM (2.8-fold), with nitrogen flux values of 801, 817, and 955 g-N m -2 d -1 for synthetic, food, and livestock wastewater, respectively, at a current density of 25 mA cm -2 and a loading rate of 2.5 mL cm -2 h -1 . Successful upscaling to an 8-cell stack, capable of treating 100 L every 20 hours (recovering 207 g-N d -1 ) of synthetic wastewater, showcases the feasibility of upscaled electrochemical systems for TAN recovery.